The Implementation of Islamic Education Axiology through Quizizz Media to Increase Students' Interest in Learning - Binti Muawanah; Ari Purnomo; Ari Hesti Fauzi; Annisa Noer Maydifika; Fitri Nur Hidayati; Imam Sayuti; Lisnawati; Muhammad Amir; Nirmala Ade; Pita Andri Yani (Bulletin of Science Education, 2021)
Education is an important pillar in the formation of students' morals and characters. In Islamic education, moral and ethical values ​​must be instilled in the younger generation. The purpose of this study is to apply ideas about the axiology of Islamic education by using the Quizizz platform to encourage students' interest in learning. The method used is a qualitative approach with a descriptive approach with students as research subjects. The results of the study showed that Quizizz increased students' interest in learning Islamic Religious Education. Quizizz showed increased student participation in class, increased their desire to learn, and better understanding of the subject matter. Thus, Quizizz is a good effective learning media to incorporate Islamic values ​​into digital-based education. Quizizz also offers interesting, attractive learning, in accordance with the development of the modern digitalization era which offers attractive features so that learning is more meaningful in implementing the axiology of Islamic Education according to the demands of the times. Keywords:  Islamic Education, Axiology, Quizizz Media